(untitled) (Journal of Engineering, 2011)
Agent technology has a widespread usage in most of computerized systems. In this paper agent technology has been applied to monitor wear test for an aluminium silicon alloy which is used in automotive parts and gears of light loads. In addition to wear test monitoring، porosity effect on wear resistance has been investigated. To get a controlled amount of porosity, the specimens have been made by powder metallurgy process with various pressures (100, 200 and 600) MPa. The aim of this investigation is a proactive step to avoid the failure occurrence by the porosity. A dry wear tests have been achieved by subjecting three reciprocated loads (1000, 1500 and 2000)g for three periods (10, 45 and 90)min. The weight difference after each test is immediately measured to find the losing weight and wear rate for each specimen. Wear test was monitored online by two sensors, force sensor to control the applied load, find friction force and coefficient of friction. The sensor is an acoustic emission to detect crack initiations of the worn surface by transfers the emitted ultrasonic waves from crack initiations to electric signals. Scanning electron microscope has been used to examine the worn surfaces. The overall results include that the effect of pores depends on pore shapes, sizes and concentrations.